2018
DOI: 10.1177/2055217318768330
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of systemic lupus erythematosus and multiple sclerosis. A case report and literature review

Abstract: Multiple sclerosis (MS) and systemic lupus erythematous (SLE) are autoimmune diseases, the coexistence of which is uncommon in patients. Owing to the rarity of this condition, the distinction between MS and SLE is a diagnostic challenge for neurologists. We present a case report in which MS and SLE were present in the same patient. There are few case reports in the world on the association between MS and SLE. The following case report is the first of its kind in which both MS and SLE are present in a patient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…True co-existence of lupus and MS is uncommon ( 19 , 87 ), and there is no convincing evidence that lupus can cause an MS-like syndrome ( 87 ). In patients with both lupus and convincing clinical and paraclinical evidence of MS ( 88 ), a more plausible explanation is that, as is sometimes seen autoimmunity, the two diseases co-exist in a single individual ( 89 ). This presents a specific management challenge of identifying immunotherapies that might offer efficacy against both diseases.…”
Section: Clinical Approach In Neurolupusmentioning
confidence: 99%
“…True co-existence of lupus and MS is uncommon ( 19 , 87 ), and there is no convincing evidence that lupus can cause an MS-like syndrome ( 87 ). In patients with both lupus and convincing clinical and paraclinical evidence of MS ( 88 ), a more plausible explanation is that, as is sometimes seen autoimmunity, the two diseases co-exist in a single individual ( 89 ). This presents a specific management challenge of identifying immunotherapies that might offer efficacy against both diseases.…”
Section: Clinical Approach In Neurolupusmentioning
confidence: 99%
“…Among them, multiple sclerosis and anti-aquaporin-4 antibody (AQP4) mediated neuromyelitis optica (NMO) may be difficult to distinguish clinically from SLE myelitis. 21,22 Differentiating between these three conditions is important because they require different treatment approaches. 23, 24, 25 Thus, we sought to compare the demographic, clinical, laboratory, and radiographic characteristics of these three conditions within an SLE registry from a large academic hospital in Boston, Massachusetts (MA).…”
Section: Introductionmentioning
confidence: 99%
“…Disorders due to systemic autoantibodies, which include ANAs, ENAs, RFs, and ANCAs, affect multiple organs or systems. Several previous reports have found the idiopathic inflammatory demyelinating diseases have positive systemic autoantibodies and comorbidities with systemic autoimmune disorders (5,14). In our previous study, we found 25.8% NMOSD comorbidities with systemic or organspecific autoimmune disorders (6).…”
Section: Discussionmentioning
confidence: 49%